2010
DOI: 10.1097/sla.0b013e3181b5ae43
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Outcomes of Cytoreductive Surgery and Perioperative Intraperitoneal Chemotherapy at a Single Tertiary Institution

Abstract: The morbidity and mortality rates of CRS and PIC are within an acceptable range for a major gastrointestinal surgery which is performed with a curative intent. Patient selection is important in ensuring that suitable patients receive this treatment. A new perspective of this treatment needs to be sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 27 publications
6
39
2
2
Order By: Relevance
“…Large case series have shown that CRS/HIPEC can be performed with acceptable morbidity and mortality rates, which could be confirmed by analysis of our own patient cohort. 8,25 However, major complications being a risk factor for long-term survival has only come into focus recently, with conflicting results. 26 A recent study found postoperative complications requiring interventions to be predictive of early recurrence in CRC patients and consequently impaired OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large case series have shown that CRS/HIPEC can be performed with acceptable morbidity and mortality rates, which could be confirmed by analysis of our own patient cohort. 8,25 However, major complications being a risk factor for long-term survival has only come into focus recently, with conflicting results. 26 A recent study found postoperative complications requiring interventions to be predictive of early recurrence in CRC patients and consequently impaired OS.…”
Section: Discussionmentioning
confidence: 99%
“…29 Infectious complications are among the most frequent after CRS/HIPEC. 25,[29][30][31] Extensive surgical trauma as well as sepsis lead to a phase of immunosuppression termed compensatory anti-inflammatory response syndrome after an initial proinflammatory state known as systemic inflammatory response syndrome. 32,33 Occurrence of complications might therefore disturb the already delicate postoperative immunological balance in these patients, multiplying the postoperative immunosuppressive state.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the existing knowledge in the literature mainly reflects the long-standing experience of those tertiary centers. CRS and HIPEC is associated with a significant morbidity and mortality; even in high volume institutions, the mortality rate is reported between 0.9%-5.8% and the reported rate of major or grade Ⅲ/Ⅳ morbidity is between 12%-52% [8,[10][11][12][13]15,18,[24][25][26][27][28] . Some authors have emphasized the importance of a learning curve in performing this technique safely and effectively [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The most serious morbidity was grade 3 ileus in three of our patients. We did not experience other surgical complications which are frequent after this procedure such as abdominal abscesses, perforations, fistulas or anastomotic leaks [28] . We believe that prior training on CRS and HIPEC technique, through fellowship training, is important for good surgical outcomes as well as the additional cooperation of experienced colorectal and hepatobiliary surgeons to make multi-organ resections safe.…”
mentioning
confidence: 99%
See 1 more Smart Citation